Pregnant women's perspectives on integrating preventive oral health in prenatal care - A. Adeniyi; L. Donnelly; P. Janssen; C. Jevitt; B. Kardeh; H. von Bergmann; M. Brondani (BMC, 2021)
Abstract Background Oral diseases are considered a silent epidemic including among pregnant women. Given the prevalence of oral conditions among pregnant women and the reported association with adverse pregnancy outcomes, there have been suggestions for the inclusion of preventive oral care in routine prenatal care. However, due to the different administrative and funding structure for oral health and prenatal care in Canada, progress towards this integration has been slow. Our study sought to qualitatively explore the views of pregnant women in British Columbia (BC) on the strategies for integrating preventive oral health care into prenatal care services. Methods A qualitative approach was utilized involving semi-structured interviews with fourteen (14) purposefully selected pregnant women in Vancouver and Surrey, BC. The interviews were audio-recorded and transcribed. The transcripts were analyzed using an inductive thematic approach. Study validity was ensured via memoing, field-notes, and member checking. Results Interviews ranged from 28 to 65 min producing over 140 pages of transcripts. Analysis resulted in three major themes: oral health experiences during pregnancy, perspectives on integration and integrated prenatal oral care, and strategies for addressing prenatal oral health care. A majority of participants were supportive of integrating preventive oral care in routine prenatal services, with referrals identified as a critical strategy. Oral health education was recognized as important before, during, and after pregnancy; oral health assessments should therefore be included in the prenatal care checklist. Limited funding was acknowledged as a barrier to oral health care access, which may explain why few participants visited their dentists during pregnancy. Interprofessional education surfaced as a bridge to provide prenatal oral health education. Conclusion Pregnant women interviewed in this study support the inclusion of educational and preventive oral care during prenatal care, although their views differed on how such inclusion can be achieved in BC. They advocated the establishment of a referral system as an acceptable strategy for providing integrated prenatal oral health care.